"Properties of solution polymerized styrene-butadiene rubber/silica composites modified by epoxidized solution polymerized styrene-butadiene rubber" - XIAO Tong-chang1, LI Xiang-yu1, QU Xiao2, DU Ai-hua1 (Hecheng xiangjiao gongye, 2024)
The effect of epoxidized solution polymerized styrene-butadiene rubber (SSBR) with an epoxy degree of 15% on the processing properties, silica dispersion, physical and mechanical properties, and dynamic mechanical properties of SSBR/silica composite was studied. The results showed that the addition of epoxidized SSBR slowed down the vulcanization rate of the composites, and the content of bound rubber in the rubber compound increased. The tensile stress, wear resistance, and resilience of SSBR/silica vulcanizates were improved, while the compression heat build-up was reduced. At the same time, the wet slip resistance of the vulcanizates was improved, and the rolling resistance was reduced.